Some Properties of Solutions of Second-Order Linear Differential Equations. (30th January 2013) - Latreuch, Zinelaâbidine; Belaïdi, Benharrat
Abstract : We study the growth and oscillation of g f = d 1 f 1 + d 2 f 2, where d 1 and d 2 are entire functions of finite order not all vanishing identically and f 1 and f 2 are two linearly independent solutions of the linear differential equation f ′′ + A ( z ) f = 0 .